Impact of COVID-19 on care of cancer patients in department of surgical oncology under the Government of Tamil Nadu: a multicentre study - Shanmugam, Subbiah; Kumar, Dakshinamurthy Suresh; Muthuvel, Ramesh; Jeevarajan, Sakthi Usha Devi; Fells, Prinith Siga; Ananthakrishna, Sandhya Pandeshwara (International Journal Of Community Medicine And Public Health, 2022)
Background: The novel corona virus has spread across world and has affected more than 200 countries and territories. The WHO declared this as ‘Public Health Emergency of International Concern’ on January 30, 2020 and since then countries all around the world are struggling to prevent their health system from collapsing due to the heavy burden of the disease. Our study was an attempt at capturing the impact of the pandemic on care for cancer patients in surgical oncology departments of different government institutions in the state of Tamil Nadu, India. Methods: Total of 5 institutes participated in this study and the hospital records of the department of surgical oncology of institutions were evaluated from January 2019 to May 2021. The available data from prepandemic year was collected and compared to that of pandemic year. Results: There was a fall of 18.1% and 18.8% in the out-patient and inpatient census, 52.09% and 28.5% in laparoscopic and open surgeries during first wave. The infection rate among patients was 0.99% (42 patients) and 3.86% (58 patients) in first and second wave & that among health workers was 15.7% and 15.3%. 88.6% of doctors and 25.3% of other health care workers were vaccinated. Conclusions: The fear of pandemic along with the measures to contain the same have disrupted care for cancer patients posing risk of disease progression and upstaging. Infection rate is high among health care personnel and vaccination coverage is suboptimal.